(untitled) (Bangladesh Journal of Agricultural Research, 2017)
On-farm experiment was carried out for four consecutive seasons: Boro (dry season) 2011-12, Transplanted Aman (T. Aman, wet season) 2012, Boro 2012- 13 and T. Aman 2013 at the farmer’s field in Londonipara, Sonagazi, Feni to develop fertilizer recommendation for rice-based cropping systems in saline and charland ecosystem in Bangladesh. The experiments were designed with eight treatments and laid out in randomized complete block design (RCBD) with three replications. The treatment combinations were: T1 = 100% NPKSZn (STB), T2 = T1 + 25% N, T3 = T1 + 25% NP, T4 = T1 + 25% NK, T5 = T1 + 25% PK, T6 = T1 + 25% NPK, T7 = 75% of T1 and T8 = Absolute control. Results indicated that application of different fertilizers significantly affected the grain yield at all of the seasons. In Boro 2011-12, the highest grain yield was found in treatment T1 (100% STB) while T3 (T1 + 25% NP) gave highest grain yield in Boro 2012-13. Statistically identical yield was observed in Boro 2011-12 with all treatments except control (T8). Highest grain yield was found with T6 (T1 + 25% NPK) treatments in both of T. Aman 2012 and 2013 seasons. Annual straw yield was found more in T6 (T1 + 25% NPK) treatment. All the treatment combinations gave significantly higher yield over the control in all seasons. However, on the basis of yield performance, economic analysis and nutrient absorption, the treatment T6 = T1 + 25% NPK (N225P30K17.5S15Zn4 for Boro and N121P15K9S10Zn3 for T. Aman) performed the best among the treatments. Bangladesh J. Agril. Res. 42(3): 521-529, September 2017